IMPLEMENTATION OF BALANCED SCORECARD AS A STRATEGIC MANAGEMENT TOOL IN FINANCIAL SERVICES COMPANIES - HARIADI (Digital Economy and Digital Transformation Review, 2023)
The purpose of this study was to analyze the implementation of the Balanced Scorecard as a marketing strategy for service companies. The method used in this research is qualitative. The data generated is descriptive data in the form of written or spoken which can be observed within a certain range from a comprehensive perspective. This study uses a literature study with a content analysis approach. The data used is secondary data in the form of writing sourced from articles and books. The results of the study show the need for a balance of financial and non-financial aspects which include: (a) a financial perspective. A good financial aspect then this indicates the good health of the company's performance, thus creating a positive perception for consumers. (b) Customer Perspective. Service companies need marketing strategies that are in accordance with the target market or market segments. The marketing strategy that can be used is a digital marketing strategy. Digital marketing strategies enable service companies to reach a wider market segment. (c) Internal Business Process Perspective. Service companies need to provide value propositions that are able to attract and retain customers in the desired market segment and satisfy shareholders. Internal business processes can be carried out through innovation processes, operational processes and after-sales services. (d) Learning and Growth Perspective. Service companies need to provide the infrastructure for achieving a financial perspective, a customer perspective, and a process perspective to generate long-term growth and improvement. It is important for a company when investing not only in equipment to produce products or services, but also investing in infrastructure, namely: human resources, systems and procedures.